2019
DOI: 10.5334/irsp.222
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Social Thermoregulation and Risk Avoidance Questionnaire (STRAQ-1)

Abstract: Development and Validation of the Social Thermoregulation and Risk Avoidance Questionnaire (STRAQ-1) How do interpersonal relationships form and what are they for? Bowlby's (1969) model of interpersonal relationships proposed that caregivers (early in life) and partners (later in life) serves as a secure base from which to explore. The concept of interpersonal attachments has been associated with nearly every important aspect of human psychology, ranging from individual differences in emotion regulation (Frale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…5 In half of our sample, the correlation between solitary thermoregulation and sex was r = .31, p < .001 and the correlation between social thermoregulation and sex was r = .04, p = .44. Furthermore, Vergara et al (2019) found a link between thermoregulation variables and the relationship status and we might expect similar relation in our sample as well. In half of our sample, the correlation between solitary thermoregulation and the relationship status was r = -.11, p = .09 and the correlation between social thermoregulation and the relationship status was r = .22, p < .001.…”
Section: Mediation Modelssupporting
confidence: 84%
See 3 more Smart Citations
“…5 In half of our sample, the correlation between solitary thermoregulation and sex was r = .31, p < .001 and the correlation between social thermoregulation and sex was r = .04, p = .44. Furthermore, Vergara et al (2019) found a link between thermoregulation variables and the relationship status and we might expect similar relation in our sample as well. In half of our sample, the correlation between solitary thermoregulation and the relationship status was r = -.11, p = .09 and the correlation between social thermoregulation and the relationship status was r = .22, p < .001.…”
Section: Mediation Modelssupporting
confidence: 84%
“…The STRAQ-1 was created and validated to investigate whether people's strategies to thermoregulate relate to their feelings of reliability and safety in relationships. And indeed, Vergara et al (2019) found that people's desires to socially and solitarily thermoregulate respectively relate to avoidance and anxiety in relationships. The STRAQ-1 thus provides not only a valid measurement tool, but also shows that people's ways of coping with the environment relate to their attachment styles.…”
Section: Postulated In Hismentioning
confidence: 99%
See 2 more Smart Citations
“…The Social Thermoregulation and Risk Avoidance Questionnaire (STRAQ-1; Vergara et al, 2019) is composed of 23 items and 4 subscales. The most important scales for this type of research are the Social Thermoregulation subscale (exploratory sample: α = 0.77; ω h : 0.64; ω t : 0.89; confirmatory sample: α = 0.65; ω h : 0.64; ω t : 0.88; sample item: "When I feel cold I seek someone to cuddle with"), which measures individual differences in the desire to rely on other people to regulate temperature; the Solitary Thermoregulation subscale (exploratory sample: α = 0.82; ω h : 0.45; ω t : 0.94; confirmatory sample: α = 0.87; ω h : 0.66; ω t : 0.93; sample item: "When I feel cold I don't turn on the heater"), which measures individual differences in the degree to which people desire to regulate temperature by themselves; and high temperature sensitivity (exploratory sample: α = 0.91; ω h : 0.68; ω t : 0.98; confirmatory sample: α = 0.88; ω h : 0.75; ω t : 0.94; sample item: " I am sensitive to heat").…”
Section: Questionnaire Detailsmentioning
confidence: 99%